2021
DOI: 10.31436/iiumej.v22i1.1364
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and Production of Poly (Lactic Acid)/Poly(ethylene Glycol) Microfiber via Melt Drawn Spinning Process

Abstract: In this study, melt blended compositions of pure PLA with additions of polyethylene glycol (PEG) up to 30 wt% were prepared. Fourier-transform infrared spectroscopy (FTIR), differential scanning calorimeter (DSC), and thermogravimetric analysis (TGA) were used to investigate the properties of PLA/PEG blends, such as structural, thermal, and morphological properties. The results showed that further increments of PEG cause the -OH group of PLA/PEG blends to show a broad peak, indicating that there is hydrogen bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
2
3
0
Order By: Relevance
“…The alignment of macromolecules of such filaments was low, and the rosin worked as a plasticizer that facilitated the PLA chain's mobility, which improves filament drawability. Such results correlate with the works of other authors [39][40][41][42][43]: that a low plasticizer concentration decreases the linear density of multifilament yarns when used under the same conditions of formation and, consequently, multifilament yarns with lower linear density and diameter are formed (comparing A with B and C). When the draw ration of PLA multifilament yarns is 2.75, the alignment of the macromolecules of filaments is higher and multifilament yarns with a lower linear density and thinner filaments are formed (see Table 2).…”
Section: The Influence Of Rosin On the Linear Density And Mechanical Propertiessupporting
confidence: 91%
See 1 more Smart Citation
“…The alignment of macromolecules of such filaments was low, and the rosin worked as a plasticizer that facilitated the PLA chain's mobility, which improves filament drawability. Such results correlate with the works of other authors [39][40][41][42][43]: that a low plasticizer concentration decreases the linear density of multifilament yarns when used under the same conditions of formation and, consequently, multifilament yarns with lower linear density and diameter are formed (comparing A with B and C). When the draw ration of PLA multifilament yarns is 2.75, the alignment of the macromolecules of filaments is higher and multifilament yarns with a lower linear density and thinner filaments are formed (see Table 2).…”
Section: The Influence Of Rosin On the Linear Density And Mechanical Propertiessupporting
confidence: 91%
“…The alignment of macromolecules of such filaments was low, and the rosin worked as a plasticizer that facilitated the PLA chain's mobility, which improves filament drawability. Such results correlate with the works of other authors [39][40][41][42][43]: that a low The linear density (tex) of melt-spun PLA yarns depends on the different technological parameters (melt temperature, draw, and pressure) [13,34]. If the draw ratios increase, the linear density of the PLA multifilament yarns decrease (34-39%), all other spinning variables remaining constant.…”
Section: The Influence Of Rosin On the Linear Density And Mechanical Propertiessupporting
confidence: 89%
“…The FTIR spectra of FFA lard showed fatty acid peaks at ~1735–1710 cm −1 and 720 cm −1 , which contribute to the source of carboxylate ions, such as stearate [39]. In addition, any band structures observed between 1440 and 1395 cm −1 are almost exclusively indicative of symmetric stretching vibration of the carboxylate group [40]. Furthermore, Coates and Meyers concluded that the strong methyl band between 1415 and 1470 cm −1 and the methylene rocking vibration at 725–720 cm −1 indicate a long‐chain linear aliphatic structure [41].…”
Section: Resultsmentioning
confidence: 99%
“…The blend of PLA/PCL is also used in electrospinning to make nanofibers [242]. Moreover, Akhir et al [243] used polyethylene glycol (PEG) in the 5-30 wt% range to blend with PLA and make finer fibers. This is attributed to the plasticization effect of PEG.…”
Section: Blend and Composite Fibersmentioning
confidence: 99%
“…Figure 7. Some photos from melt-spun biodegradable polymer fibers: (a) PBS fibers with 30 micron diameter[117], (b) BC-treated PCL fiber[257], (c) PLA fibers containing 5% soy[224], (d) 3D woven structure from PLA fibers derived from PLA/PVA blend[235], (e) PLA/PLA-g-MA/MCC composite fiber[233], (f) PCL monofilament with Snowflake cross-section[198], (g) Hollow fiber of PHB/PCL 70/30[211], (h) PHBH monofilaments one-step-drawing after 24 isothermal crystallization[167], (i) Surgical knot on PHBH monofilament[193], (j) Irregularity (necking point) on drawn r-PLA filament[200], (k) Extracted PLLA nanofibers from PLLA/LDPE[236], (l) Hollow PHB fibers[258], (m) PLA/PEG fibers[243], (n) F-actin (magenta) and cell nuclei on PGA fibers[123], and (o) porous ultrafine PGA fibers by dissolving PLA in spun blend fiber[238]. All the figures were reprinted with permission from the publishers.…”
mentioning
confidence: 99%